(untitled) (Research, Society and Development, 2021)
Objective: To assess the association between leisure-time physical inactivity (IFL) and common mental disorders (CMD) among Primary Health Care (PHC) workers. Methods: Cross-sectional study, carried out with a random sample of 2,136 PHC workers from municipalities in the state of Bahia. The data collection questionnaire included sociodemographic and occupational characteristics, lifestyle and the Self-Reporting Questionnaire. Multivariate analysis was performed using Poisson Regression with robust variance. Results: Prevalences of 22.6% for CMD and 48.2% for IFL were identified. In the bivariate analysis, there was a higher prevalence of CMD in those with IFL (p <0.001), female gender (p = 0.015), lower level of education (p = 0.001) and income (p <0.001), in Community Health Agents (p <0.001), with a working time of five years or more (p = 0.040) and sedentary behavior at leisure (watching TV and / or listening to the radio) (p = 0.025). There was an increase in the prevalence of CMD among those with IFL (53%), with time spent in the unit greater than or equal to five years (20%) and whose activities in their leisure time were watching TV and listening to the radio (30%). In the multiple analysis, the association between IFL and CMD remained significant (PR: 1.36; 95% CI: 1.11-1.65), adjusting for the confounding variables. Conclusion: IFL is an important determinant of the occurrence of CMD among PHC workers, influenced by the characteristics of the organization and work process and other leisure life habits in this relationship.